Western Flower Thrips (Frankliniella occidentalis [Pergande]) - Jeffery D. Cluever; Hugh A. Smith; Joseph E. Funderburk; Galan Frantz (EDIS, 2015)
One of many species of thrips found in Florida, Frankliniella occidentalis, is a pest of several crops throughout Florida and the world, causing injury by feeding and by transmission of plant viruses. This 8-page fact sheet was written by Jeffrey D. Cluever, Hugh A. Smith, Joseph E. Funderburk, and Galen Frantz, and published by the UF Department of Entomology and Nematology, April 2015. (Photo: Lyle Buss)